Sorption of phenols and flavonoids on activated charcoal improves protein metabolism, antioxidant status, immunity, and intestinal morphology in broilers - Zhang, Ying; Fu, Xiaoqi; Wang, Lixue; Guo, Xiangyue; Dong, Bing (Frontiers in Veterinary Science, 2024)
Previous studies have revealed that activated charcoal sorption of Chinese herbal extracts is more effective than activated charcoal. The present study was designed to investigate whether phenols and flavonoids have an effect on nutrient metabolism, antioxidant activity, immunity, and intestinal morphology in broilers. Seven diets [basal diet (CON); CON supplemented with 450 mg/kg of activated charcoal (AC); CON supplemented with 250, 500, 750, 1,000, or 7,500 mg/kg of phenolic acids and flavonoids (PF) to AC (PFAC)]. PFAC was the complex of AC sorption of PF in the ratio of 9:1. These dietary treatments for broilers lasted for 42 days. Results showed that at d 21, all doses of PFAC altered serum levels of total protein, albumin, and creatinine compared to AC (p < 0.05). Both PFAC and AC altered HDL-, LDL-, and VLDL-cholesterol levels compared to CON (p < 0.05). PFAC at 500 mg/kg (450 mg/kg AC+ 50 mg/kg phenolic acids and flavonoids) increased serum IgA and IgM (p < 0.05), but AC at 450 mg/kg did not, compared to CON. At d 42, breast and thigh muscles of PFAC-treated broilers had higher free radical scavenging activities compared to CON (p < 0.05), but AC had no such effect. PFAC at 500 mg/kg increased villus height in the duodenum, jejunum, and ileum compared to CON (p < 0.05), but AC had no such response. PFAC at 500 mg/kg effectively improved protein and lipid metabolism, antioxidant status, and intestinal morphology, but AC had no such effect at a similar dose. Excessive PFAC (7,500 mg/kg) showed no significant side effects on broiler growth, liver damage, or hematology. These results suggest that phenols and flavonoids, in cooperation with activated charcoal, provide the majority of the functions of the herbal extract from multiple Chinese medicinal herbs.